Short Communication: Agronomical characteristics of sweet corn under different plant growth regulators during the dry season (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mubarok S, Wicaksono FY, Nuraini A, Rahmat BPN, Budiarto R. 2022.S hort Communication: Agronomical characteristics of sweet corn under different plant growth regulators during the dry season. Biodiversitas 23: 3091-3098. Sweet corn (Zea mays convar. saccharata var. rugosa)is one of the important horticultural crops. Increasing sweet corn production during the dry season can be achieved by applying plant growth regulators (PGR). PGRs such as auxin, gibberellin, cytokinin, ethylene, and other phytohormones control various physiological and chemical processes in plants. The PGR is often used for the engineering process of plant cultivation technology, especially during environmental stress conditions. This study aimed to determine the effect of PGRs (auxin, gibberellic acid, salicylic acid, and paclobutrazol) on sweet corn growth and yield during the dry season. The results showed that the application of PGR significantly affected sweet corn growth, yield, and yield quality during the dry season. The auxin significantly increased plant height and leaf length, whereas paclobutrazol and salicylic acid significantly increased the number of cobs and total soluble solids of sweet corn, respectively.